Interdisciplinary Approaches in ELT: Semiotics, AAC Systems, and Neuroscience - Mata, Irma Isela Cipres (Journal of Posthumanism, 2025)
The study aimed to determine the qualitative impact of semiotic, neurocognitive, and psychoanalytic approaches combined with Augmentative and Alternative Communication (AAC) Systems in English Language Teaching (ELT) within Teacher Training Schools across Mexico. Three-phase interventions were applied (Eco, 1976; Barthes, 1957; Kramsch, 2013; Kress, 2010), alongside semi-structured in-depth interviews and classroom observations (Krashen, 1982; Damasio, 1994; LeDoux, 1996; Siegel, 2012; Vygotsky, 1978; Gardner, 1985). The results highlighted the positive impact of interdisciplinary semiotic approaches and AAC Systems (Tedesco, 2012; García & Domínguez, 2007; Cavanaugh, 2009; Siegel, 2012) in fostering semiotic learning environments for ELT (Damasio, 1994; Phelps, 2006; Goleman, 2006; Zembylas, 2005; Krashen, 1982).